2018
DOI: 10.1161/hypertensionaha.118.10908
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Maternal Diabetes Mellitus Causes Renal Dopamine D 1 Receptor Dysfunction and Hypertension in Adult Rat Offspring

Abstract: Epidemiological and experimental studies suggest that maternal diabetes programs hypertension that is associated with impaired sodium excretion in the adult offspring. However, the underlying mechanisms are not clear. Because dopamine receptor function is involved in the pathogenesis of hypertension, we hypothesized that impaired renal dopamine D1 receptor function is also involved in the hypertension in offspring of maternal diabetes. Maternal diabetes was induced by a single intraperitoneal injection of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 58 publications
(124 reference statements)
1
7
0
Order By: Relevance
“…One potential neuroprotective agent, dopamine (DA), is a key neuromodulator found throughout the body and within the retina, where it is released by dopaminergic amacrine cells. Diabetic animals have DA deficiencies in the retina (13), brain (19), and kidneys (20). When diabetic rodents are treated with levodopa (L-DOPA), a precursor to DA that crosses the blood-brain and blood-retina barriers, DA levels as well as early OP delays to dim-flash stimuli are restored (13).…”
mentioning
confidence: 99%
“…One potential neuroprotective agent, dopamine (DA), is a key neuromodulator found throughout the body and within the retina, where it is released by dopaminergic amacrine cells. Diabetic animals have DA deficiencies in the retina (13), brain (19), and kidneys (20). When diabetic rodents are treated with levodopa (L-DOPA), a precursor to DA that crosses the blood-brain and blood-retina barriers, DA levels as well as early OP delays to dim-flash stimuli are restored (13).…”
mentioning
confidence: 99%
“…Our previous study showed that LPS exposure during pregnancy leads to impaired renal sodium excretion and hypertension in the offspring attributable to oxidative stress, caused by decreased antioxidant capacity, resulting in the accumulation of reactive oxygen species (ROS) in the kidney. 8 To determine the oxidative stress level in the rats with transgenerational inherited hypertension induced by PLPS exposure, we measured the serum levels of malondialdehyde, a lipid peroxidation product used as an indicator of oxidative stress in the whole body, 31 in F0 to F3 control and PLPS offspring. The serum malondialdehyde levels, measured by ELISA, were significantly increased in F0 and F1 PLPS offspring compared with control rats but decreased to control levels in the F2 and F3 offspring (Figure 5A1).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11]14,20,[30][31][32] Our previous studies and those of others have shown that activation of dopamine D 1 -like receptors (D 1 and/or D 5 receptors) inhibits NKA activity in RPT cells. [6][7][8][9][10][11]14,20,[30][31][32][33][34] However, the role of D 4 receptor activation in regulating renal NKA activity remains unclear. The present study showed that activation of D 4 receptors in WKY RPT cells inhibits NKA activity in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%